International live insect trade: a survey of stakeholders - OLIVA,CF; CHAND,R; PRUDHOMME,J; MESSORI,S; TORRES,G; MUMFORD,JD; DEME,I; QUINLAN,MM (Revue Scientifique et Technique de l'OIE, 2022)
There are significant numbers of transboundary shipments of live insects for pollination, pest management, industrialprocesses, research and other uses, but data collection and analysis have proved difficult. The World Organisation forAnimal Health and Collectif TIS (Technique de l’Insecte Stérile), a French think tank, carried out a stakeholder surveyto understand the nature of the live insect trade and potential challenges to safety and efficiency. Target respondentshad experience in the areas of biocontrol, sterile insect technique, entomological research and regulatory affairs.Although the survey was sent globally, the responses were unintentionally biased towards Europe, where interest ishigh, since this region is developing a comprehensive framework to promote the use of beneficial insects to replacepesticides.The survey also explored respondents’ knowledge of several international agreements on the movement and riskmanagement of beneficial or invasive insects. Knowledge of the various regulations was generally poor, and respondents highlighted a perceived lack of clarity regarding live insect shipments in the existing international regulationsand guidelines. Almost two-thirds of participants reported reluctance by carriers to accept live insects for shipment,and three-quarters described occasional to systematic delays that resulted in a reduction of quality or viability. Somerespondents reported that they instead hand-carry live insects, mostly in small quantities.Participants described being directly involved in trade covering 70 species of live insects and ticks transportedamong 37 countries, with volumes ranging from fewer than ten insects to over a million per shipment. Of these, 30%were potential vectors of pathogens to humans or animals, 42% were potential plant pest species (including someused for biocontrol), and 17% were classical biocontrol agents.The results of this survey begin to define the current scope, scale and issues for t